De From colonial masonry to modern exposed brickwork Bogota’s brick workshops and their influence on urban and architectural development (1810-1920): Los chircales de Bogotá y su impronta en la arquitectura y el desarrollo urbano, período 1810-1920 (2011)
The article presents an approach to the historical evolution of Bogota’s early brick workshops, emphasizing on their contribution to architecture and urban development between 1810 and 1920. It includes an outlook of the so called Architecture of Transition, identifying styles, architects and construction materials, and it analyzes the quality of the bricks provided by those local clayworkshops during the given period, as well as their production techniques improvement. It also spots out those first buildings to expose masonry as their only façade material in industrial,residential, governmental, educational and religious architecture, and, as a conclusion, it highlights the importance of such epoch for consolidating the usage of exposed brickwork in the city, an image that defines Bogota’s architecture during the second half of the twentieth century